THE ANALYSIS OF ISLAMIC LAW ON THE NUMBER OF RAKA'AH IN THE TARAWIH PRAYER - Muarif, Yahya Zainul (Jurnal Pembaharuan Hukum, 2022)
In religion everyone has different abilities in carrying it out. What is clear is that no one is perfect in religion except for the Prophet Muhammad Pbuh., no matter how great we are in worship/prayers, we must still have flaws on the other side. This research aims to know the analysis of islamic law on the number of raka'ah in the Tarawih prayer. Likewise in thinking, different people understand or problem solving. However, if the intent is correct and the method is also correct with the correct arguments then it will lead to conclusions that can be considered correct. If the conclusion turns out to be different, intelligent people will easily understand that such a thing is normal in the world of fiqh thinking. This paper used a descriptive qualitative method through several exploratory literature studies. The resulting findings are that the Tarawih prayer in the month of Ramadan is one of the sunnah practices, but there are differences in the number of raka'at. So the conclusion in this differences can be accepted based on argumentatives and clear reasons originating from the arguments of naqli and aqli.